HEPATOPROTECTIVE PROPERTIES OF NANOSULFATE CHITOSAN ON THE MODEL OF ACUTE TETRACHLORMETHANE HEPATITIS - Zulfiya I. Galieva; Firuza Kh. Inoyatova; Vazira Rakhmanova; Rakiya Yu. Milusheva; Sayora Sh. Rashidova (Central Asian Journal of Medicine, 2024)
The effects of low molecular weight chitosan (LMWC) and nanosulfate chitosan (NSC) were studied in comparison with the classical hepatoprotector carsil on the model of tetrachlormethane acute toxic liver injury (ATLI). The optimal hepatoprotective doses of LMWC 25 microg and NSC 10 mg/kg were established for oral administration for 12 days after reproducing the ATLI model. The drugs in these concentrations restored the detoxifying function of hepatocytes, reduced the severity of cytolysis, cholestasis, mesenchymal inflammation, hepatocellular insufficiency syndromes, activated antioxidant activity and reduced high values of lipid peroxidation and apoptosis.